Hubungan Pengetahuan Orang Tua tentang Pencegahan ISPA dengan Kondisi Sanitasi Rumah di Wilayah Kerja Puskesmas Ambulu - Herlina Dwi Puspita; Lantin Sulistyorini; Eka Afdi Septiyono (Pustaka Kesehatan, 2023)
Acute Respiratory Infection (ARI) is a disease that often affects children younger than 5 years caused by viruses or bacteria. ARI can be caused by many factors, such as intrinsic and extrinsic factors. Extrinsic factors include the sanitation conditions of the house, such as occupancy density, ventilation, type of floor, humidity, lighting, and maternal factors, such as level of education, age and knowledge. This study aims to identify whether there is a relationship between parents' knowledge about ISPA prevention and the sanitation conditions of homes in the working area of ​​the Ambulu Health Center. This type of research were descriptive correlational with a cross-sectional approach with a sample of 92 respondents, with a sampling technique using simple random sampling. The results of the chi-square statistical test show the valueρ value = 0.000 (α < 0.05).Data collection was carried out using questionnaires and observation. The results showed that 19 mothers (20.7%) had moderate knowledge and 72 mothers (78.3%) had good knowledge. The sanitary condition of the respondent's house was in the moderate category of 24 (26.1) and the sanitary condition of the house was good as much as 68 (73.9%). It is hoped that health services can provide additional knowledge regarding the prevention of ARI for parents, especially those with children under five. So this can help health services to reduce the number of ARI cases, especially in rural areas that are not exposed to information.